THE CONTRIBUTION OF THE ARCHIPELAGO'S TURATH IN ADDRESSING CONTEMPORARY ISSUES Study on Tafsir Al-Ibriz by Bisri Musthofa - Ridhoul Wahidi; Fiddian Khairudin (SYAHADAH : Jurnal Ilmu al-Qur'an dan Keislaman, 2023)
This paper discusses the contribution of the archipelago's turath in answering contemporary problems, a review of the tafsir Al-Ibrîz Li Ma'rifati Tafsîr Al-Qur'ân Al-zîz by Bisri Musthofa. There are several contributions written by Bisri Musthofa in his tafsir related to contemporary issues including purification of faith, moderate attitude, social society, prioritizing the unity of the people, eliminating khurafat, and the invitation to stick to the sharia. All of them lead to the contribution of the archipelago's turath in answering and accommodating the problems that exist in society. It remains how the next generation understands and applies it in a complex life so that it remains on the path of Islam.